Question
Solve for \( z \) \[ 2(-z-1)=-4 z \] \( z=\square \) Submit
Ask by Carter Harrington. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\( z=1 \)
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Unlock
Reviewed and approved by the UpStudy tutoring team
Like
Mind Expander
To solve for \( z \), first simplify the equation: \[ 2(-z-1) = -4z \] Distributing the 2 on the left side gives: \[ -2z - 2 = -4z \] Now, add \( 2z \) to both sides: \[ -2 = -4z + 2z \] This simplifies to: \[ -2 = -2z \] Dividing both sides by -2 results in: \[ z = 1 \] So, \( z = \boxed{1} \)